Legal Compliance and Environmental Sustainability: The Case of Single-Use Plastics in Bali - Yulianti, Wahyu Erni (ANTMIND YOUTH EMPOWER FOUNDATION, 2024)
This study explores the effectiveness of regulatory measures to restrict single-use plastics in Bali, a prominent tourist destination facing significant plastic waste challenges. The Bali Regional Government implemented Bali Governor Regulation No. 97/2018, targeting reductions in plastic bags, styrofoam, and straws through obligations on producers, distributors, and businesses to offer non-plastic alternatives. Evaluations in 2020 showed notable decreases: 57% for plastic bags, 81% for styrofoam, and 70% for plastic straws. The success is attributed to stringent law enforcement, adequate facilities, and the Balinese cultural readiness for environmental change. Education and socialization also played crucial roles in public compliance. Nevertheless, challenges persist in small markets and warungs. The study underscores the need for ongoing waste management improvements, continuous public education, and traditional leadership engagement to sustain behavioral change, supported by clear incentives and sanctions.